Fatal thirst : diabetes in Britain until insulin - Furdell, Elizabeth Lane (History of science and medicine library, 2009)
Although medieval doctors knew of the disorder called diabetes, the disease they treated was rare and largely confined to young sufferers. This title examines the history of diabetes in Britain focusing on medieval treatments, Renaissance-era diabetology, and the centuries-long debate among specialists over the site and cure of the disease.